Capitalism and Religion in World History: Purification and Progress - Mosk, Carl (Routledge Studies in Modern History Ser., 2017)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication Page -- Table of Contents -- List of Figures -- List of Tables -- Preface -- Acknowledgements -- Part 1 Predation, purification, and prices -- Prologue: Fire -- Note -- Chapter 1 Idealism and materialism in economic history -- Janus -- Weber and Marx -- Definitions -- Three forms of purification: ritual, ethical, and political -- Notes -- Chapter 2 Axial thought traditions: From heroic myth to social control -- Religion of hunters and gatherers -- After the Neolithic revolution: predation, trade and giftÂ exchange -- Chiefdoms -- Heroic Age -- The masking principle -- Religious diversity -- Notes -- Chapter 3 The pendulum swing in the Greek Axial Age -- Origins -- The political pendulum swing -- The pendulum swing in Greek drama -- The pendulum swing in philosophy -- Notes -- Chapter 4 God as king in Jewish monotheism -- Kings, priests, and prophets -- Diaspora communities under one God -- Out of the Dead Sea Scrolls -- Notes -- Chapter 5 Predation, gift exchange, and markets in the Roman Empire -- Predation and empire building in the ancient world -- An ideological pendulum swing -- Notes -- Chapter 6 One God, one emperor -- More political pendulum swings -- Dominus and Deus -- The Council of Nicaea -- After Constantine the Great -- âThe City of God and the City of the Worldâ -- Notes -- Part 2 Merchant capitalism -- Chapter 7 Islamic merchant capitalism -- Consolidating Catholicism and feudalism: The great pendulum swing of early medieval Europe -- The Silk Road -- The rise of Islam -- The bill of exchange -- Notes -- Chapter 8 The pendulum swings of the High and Late Medieval West -- The pendulum swing of the High Medieval Period: simonyÂ andÂ the Crusades